(untitled) (Research, Society and Development, 2021)
This present study aims as objective: to understand the hypodermoclisis in oncologic palliative care: an infusion technique that is applied when the patient gets unable to use the venous network and the oral route in oncological cases of chronic diseases. Methodology: We carried out a descriptive exploratory study with a qualitative approach. Discussion and results: It is presented as a technique used for administering medications and electrolytes, advantage, disadvantage, installation technique, material used for puncture, length of stay, dressing maintenance. Final considerations: Thus, it is shown as a technique that is easy to apply, low cost, safe, effective, reduces patient suffering at the time of being punctured and decreasing the pain and symptoms caused by the pathology. However, the practice is still poorly recognized among health professionals, and there is a need for more dissemination and investment with institutional manuals and protocols on hypodermoclisis. In this way it will favor the recognition of the technique scientifically for nurses, academics and doctors.